Introduction: Archives and Radical Education - Dittmar, Linda; Entin, Joseph (Radical Teacher, 2016)
Though Alain Resnais’ documentary film about the French National Library, All the World’s Memory (Toute la Memoir du Monde), is meant to celebrate the library’s scope and organization, anxiety seeps into its cinematic “language”: dim black-and-white footage, a restlessly prowling camera, close-ups that cut off object from context and detail from whole, discontinuous cuts, choppy bullet-like comments, and darkly foreboding orchestral music. It’s a beautiful film, but what does it say about Resnais’ feelings about the library? Certainly awe, but also high modernism’s anxiety about proliferating knowledge. “Man,” the authoritative male voice-over proclaims, “fears being engulfed by this mass of words.”